Reflection Analysis of Impermeable Slopes under Bimodal Sea Conditions - Stephen Orimoloye (Journal of Marine Science and Engineering, 2020)
Understanding of the reflection characteristics of coastal seawalls is crucial for design. Wave reflection can cause difficulties in small vessel manoeuvring at harbour entrances; this can cause damage to the toe of coastal structures by scouring. Previous studies have examined the reflection characteristics of coastal seawalls under random wind-generated waves without considering the effects of wave bimodality created by the presence of swell waves. This present study focuses on the influence of random wave bimodality on the reflective characteristics of coastal seawalls. 823 experimental tests were conducted to examine the reflection performance of impermeable sloping seawalls under bimodal waves. Reflection coefficients were computed from each test. The analysis of the results suggests that both unimodal and bimodal waves give similar reflection characteristics. However, the reflection coefficient in bimodal sea states seems to be more prolonged than in the unimodal sea states. It was found that the reflection coefficients of coastal seawalls are strongly influenced by the seawall slope, the wave steepness, the relative water depth, and the surf similarity parameters. A new empirical reflection equation to describe the influence of wave bimodality on the reflection characteristics of coastal seawalls has been formulated based on this study.